ANALISIS PASOKAN BAHAN BAKU PISANG DENGAN PEMILIHAN PEMASOK PADA UKM AYUMI PASTRY - Sinta Verda Ningsih, Sinta; Sumantika, Arsyad (LPPM Universitas Putera Batam, 2024)
Supplying raw materials and selecting suppliers is one of the most important things in producing quality products. UKM Ayumi Pastry experienced problems in managing the supply of banana raw materials optimally and experienced problems determining the best banana supplier. In this research, raw material inventory processing was carried out using the Economic Order Quantity (EOQ) method and supplier selection using the Analytical Hierarchy Process (AHP) method. The aim of this research is to analyze the supply of banana raw materials by selecting selected suppliers and ordering economical supplies. Control of raw materials using the EOQ method, namely economical ordering by placing 20 orders in 2023, the order quantity is 217.29 kilograms. Meanwhile, according to Ayumi Pastry's policy, this is done 13,25 times with an order quantity of 371 kilograms. The TIC according to EOQ for the costs incurred is Ro889,943 less than the costs incurred by the UKM Ayumi Pastry policy. For the AHP method, the supplier selected is Supplier A as the main priority in fulfilling banana raw materials with a weight of 0.5245 and Supplier B as a backup supplier in fulfilling banana raw materials is in Rank III with a weight of 0.1929.